Design of MnOx/TiO2 Nanostructures for Photocatalytic Removal of 2,4‐D Herbicide - Angeles Mantilla; Sandra Cipagauta Díaz; Enrique Samaniego Benitez; Francisco Javier Tzompantzi Morales; Michelle Navarrete Magaña (ChemistryOpen)
Abstract The research and modification of semiconductors through different synthesis routes allow obtaining materials with optimal properties to induce new energy levels and improve charge separation efficiency. In this context, the sol‐gel method was used to synthesize TiO2‐based materials doped with different percentages of MnOx to evaluate their photocatalytic activity in the degradation of the herbicide 2,4‐dichlorophenoxyacetic acid (2,4‐D) in water under UV irradiation. Characterization results revealed a reduction in crystallite size to 7.2 nm. Adding MnOx enhanced the optical absorption of TiO2, resulting in a shift toward the red end of the spectrum of the forbidden energy band. The photocatalytic activity increased significantly with the percentage of MnOx, reaching a maximum degradation of 70 % in 6 hours with the 3 MnTi material. This increase was attributed to the synthesis method, which facilitated the formation of nanostructured heterojunctions mainly composed of TiO2 and MnO2, reducing the recombination of electron‐hole pairs. TEM analysis confirmed these structures. A reaction mechanism for the 3 MnTi material is proposed, considering the mobility of charge carriers and the photooxidation processes of the pollutant.